La propagande anti-britannique en France pendant l’Occupation - Françoise Passera (Revue LISA)
Left to fight alone after France signed the armistice on the 22nd of June 1940, Great Britain became enemy number one in the eyes of the German occupying forces and the Vichy government. This hostility found expression in a considerable quantity of propaganda in the guise of posters, tracts, booklets and brochures meant to denounce British responsibility for the conflict in the eyes of French public opinion. Propaganda was particularly intense from June to December 1940 and from January to June 1944 but the German and French propaganda services waged this psychological warfare against Great Britain throughout the war. In 1940, the anti-British brainwashing campaigns aimed at ridding the defeated French of their guilt by accusing the ex-ally of being the cause of the conflict and of deceit during the Battle of France. In 1941-1942, the Allies’ military setbacks were the subject of tracts and brochures that ridiculed British strategic skills. Propaganda was also based on the painful history of France and Great Britain so as to convince the French that England had always tried to deprive France of her colonies and that it was what she was trying to do by maintaining her presence in Africa. The major part of this propaganda was promoted by the German authorities, only to a lesser degree by the French collaboration parties. Till 1942, the Information Secretariat of the Vichy government distributed few anti-British tracts, concentrating its efforts on the promotion of the National Revolution. On the other hand, the first Anglo-American bombings in the Paris area provoked strong reactions in the Vichy government which then relied on the French population’s confusion and anxiety to denounce British policy. What was the impact of these anti-British speeches on the French population? The prefects’ reports on public opinion show that the plugging of Anglophobic sentiment had little influence on the French who were globally in complete support of the British even if they experienced doubt during short periods after the deadly bombings and at the approach of the Normandy landings.